Identification of Pratylenchus coffeae as a causal agent of root rot disease in Sorghum bicolor in China - Ling Qin; Fan-kang Lin; Yun-long Lv; Ze-Lin Tai; Xu Zhang; Hong-lian Li; Yu Li; Ke Wang (BMC Microbiology)
Abstract Sorghum (Sorghum bicolor) is an important food and feed crop. Root-lesion nematodes (Pratylenchus spp.) are a group of pathogenic nematodes that cause severe economic losses in various food and cash crops. This study identified diseased sorghum plants with stunted growth and brown, rotting roots in sorghum fields in Shanxi Province, China. A species of root-lesion nematode was isolated by modified Baermann funnel method and named the GL-1 population. Afterward, the GL-1 population of root-lesion nematodes was identified as P. coffeae through a combination of morphological, rDNA-ITS and rDNA-28 S D2-D3 region techniques for molecular biological identification. We also conducted greenhouse experiments to assess the parasitism and pathogenicity of GL-1 and four other P. coffeae populations on sorghum through pot inoculation. At 60 days after inoculation, the results indicated that all five populations of P. coffeae were capable of infecting and causing damage to the sorghum plants. Sorghum is a suitable host for P. coffeae (with a reproduction factor > 1). Moreover, compared with those in the control group, the aboveground fresh weights and root fresh weights of sorghum in the five inoculation groups were significantly lower, and brown spots or even necrotic rot appeared on the roots. All five populations were highly pathogenic to sorghum, but there were significant differences in pathogenicity among the populations. This study provides a scientific basis for identifying and detecting root-lesion nematodes in sorghum.